Percutaneous collagen induction as a treatment for scars Acne vulgaris: an integrative review (Research, Society and Development, 2020)
Being that microneedling is a widespread technique in the field of dermatology, this work seeks to evaluate the effectiveness of microneedling in the treatment of acne. This is a qualitative, integrative review. The terms “acne and microneedling” and “acne and percutaneous induction of collagen” and their correspondents in Portuguese were searched in the Pubmed, Sciencedirect and Scopus databases. As inclusion criteria, it was considered: a) to be clinical research b) to be available in full text c) published between 2015 and 2019 d) to be in Portuguese, English or Spanish. Texts that had no relation to the theme and duplicates were excluded. Thus, of the 108 articles presented by the search in the databases, 23 were selected by affinity to the search theme, with 38 articles excluded due to duplication and 47 because they were not related to the subject. The treatment of acne with microneedling proved to be effective and safe, little invasive and of fast recovery. Despite this, the need for more specific future research is emphasized, evaluating its combination with other treatments, the number of sessions required and the result in different degrees of scarring.